Multiethnic Teamwork as Means of Attaining Psychosocial Competence and Interpersonal Skills For Successful Transitioning From School Life Into Adulthood - Mihaela David-Izvernar; Alina Felicia Roman (Educaţia 21)
Historically multicultural European areas display a tendency towards openness and sociability that transcends mere geographics. In ensuring that the youth of diversified ethnic populations attain life skills, the school community ought to provide the means for such social capital to build networks of interethnic school and social relationships by designing guidelines to help relate and work together on school and community projects. Hence, the necessity arose for soft skills in the respective teams working towards shared goals and transferrable objectives in the framework of set task. The present article not only develops on the key concepts, but as practical application project work, it can serve as incentive for extended use in later years, a conducive toolkit along the adulthood pathway. Furthermore, the research conducted as follow-up project validation consists of a 1-5 Likert scale conducted among 81 highschoolers in West Romania. Were such multiethnic teamwork as good practice example applied in blended learning contexts, repeatedly and purposefully, interpersonal skills and effective communication, not only within the school community, but also in non-formal contexts would be acquired and attained with increased levels of trust. Thus, highschoolers would be equipped for achieving the ends set within the school educational environment, as well as for fulfilling the lifelong occupational and personal development agenda. Such project-based work, easily extensive to interschool similar multiethnic student team structures, might trigger similar proactive future attitudes for the students on the brim of maturity, whereas meaningful insights into the validated pattern will undoubtedly trigger societal active participation.